2018
DOI: 10.1002/mbo3.719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on bacterial microbiome composition in Ixodes scapularis ticks

Abstract: Ixodes scapularis , the blacklegged deer tick, is the principal vector of Lyme disease in North America. Environmental factors are known to influence regional and seasonal incidence of Lyme disease and possibly the endemicity of the disease to the northeastern and upper mid‐western regions of the United States. With a goal to understand the impact of environmental temperature on microbial communities within the tick, we investigated the bacterial microbiome of colony‐reared I. scapularis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 56 publications
7
84
2
Order By: Relevance
“…Similarly, the mean Shannon diversity index (=2.1) is in the range of what it has been previously observed in the literature for Ixodes ticks [8,20,41,42]. However, these values are commonly known to fluctuate, mainly according to the tick stages, species or localization, and are therefore difficult to compare [5,8,10,12,16,[42][43][44][45][46]. Furthermore, the fact that not all these studies used negative controls to identify potential contaminating OTUs and remove them from their datasets calls for caution in attempts to draw conclusions about these differences, particularly when we know that these OTUs can represent more than 50% of sequences detected in tick samples [22].…”
Section: • Ixodes Ricinus Microbiota Diversity and Compositionsupporting
confidence: 57%
“…Similarly, the mean Shannon diversity index (=2.1) is in the range of what it has been previously observed in the literature for Ixodes ticks [8,20,41,42]. However, these values are commonly known to fluctuate, mainly according to the tick stages, species or localization, and are therefore difficult to compare [5,8,10,12,16,[42][43][44][45][46]. Furthermore, the fact that not all these studies used negative controls to identify potential contaminating OTUs and remove them from their datasets calls for caution in attempts to draw conclusions about these differences, particularly when we know that these OTUs can represent more than 50% of sequences detected in tick samples [22].…”
Section: • Ixodes Ricinus Microbiota Diversity and Compositionsupporting
confidence: 57%
“…TIBOLA (tick-borne lymphadenopathy) syndrome in people bitten by Dermacentor reticulatus (1 male, 5 females) infected with R. raoulti is well known. Thapa et al [27] confirmed Rickettsia spp. domination in the metagenomic analysis of I. scapularis: the majority were the endosymbiotic Rickettsia buchneri which was absent in the current research.…”
Section: Discussionmentioning
confidence: 94%
“…The mechanism of Dermacentor and Ixodes feeding has a significant impact on pathogen transfer. These ticks' feeding is long-lasting and results in a large intake of vertebrate's blood [18,26,27]. Endosymbionts are also transmitted during tick meal [14].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that these studies may have been biased by detecting contaminant bacteria, coming from both extraction and amplification steps should thus not be ruled out [68]. In any case, studies recurrently support the differences of the tick microbiota according to tick life stages [63,65,66,69,70].…”
Section: Tick Stages: Larvae Vs Nymphs Vs Adultsmentioning
confidence: 96%
“…As previously mentioned, over their life-cycle, ticks are likely to experience the influence of the temporal variation of multiple factors such as temperature, hydric stress and diapause. All these factors are known to probably influence tick activity and metabolism and might potentially affect their microbiome [70]. While studies on tick microbial community diversity, composition and role have considerably increased in the past years, many questions arise about the temporal dynamics of the tick microbiome.…”
Section: Is the Temporal Scale Crucial To Study The Tick Microbiome?mentioning
confidence: 99%